Sensory profiling: a method for describing the sensory characteristics of virgin olive oil - David H. Lyon; Martin P. Watson (Grasas y Aceites)
Sensory profiling is an objective, descriptive technique which uses a panel of trained assessors. It was used at Campden to differentiate olive oil which differed in terms of the country of origin, variety, ripeness and extraction techniques. The data were related to similar results from the Netherlands and Italy. The results indicated that all three sensory panels perceived the samples in the same way, however, the differed in the way the oils were described. The new European legislation on olive oil is partially concerned with the sensory aspects of the oil. The sensory grading takes into account the 'positive' and 'negative' attributes in the oil before giving an overall quality grade. These attributes do not reflect the consumer requirements, therefore, the grading should be restricted to the assessment of the presence or absence of sensory defects.